Risk Factors of Prolonged Mechanical Ventilation in Post Coronary Artery Bypass Graft Patients: A Scoping Review - Kumalasari RI; Kosasih CE; Priambodo AP (Journal of Multidisciplinary Healthcare)
Regina Indah Kumalasari,1 Cecep Eli Kosasih,2 Ayu Prawesti Priambodo2 1Master Study Program, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Department of Critical Care and Emergency Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, IndonesiaCorrespondence: Cecep Eli Kosasih, Faculty of Nursing, Universitas Padjadjaran, Jl. Raya Ir. Soekarno KM. 21, Hegarmanah, Jatinangor, Sumedang, West Java, 45363, Indonesia, Fax +62 02287793411, Email cecep.e.kosasih@unpad.ac.idAbstract: Prolonged mechanical ventilation (PMV) following CABG surgery is associated with increased patient morbidity and mortality. A consensus has yet to be reached regarding the time limit for PMV. Various studies have identified factors that influence PMV in patients following CABG surgery, but a review has yet to synthesize the results systematically. This review aimed to identify the definition and factors associated with PMV in patients following isolated CABG surgery. This scoping review used the framework developed by Arksey and O’Malley (2005). Primary sources of information were searched through 5 databases: PubMed, Scopus, Oxford Academy, Sage, and CINAHL and two search engines: Science Direct and Google Scholar, accessed on October 25, 2023. Eight articles with a total of 12,178 participants were included in this review. The PMV time limits used in the studies varied from > 12 hours to > 48 hours. The factors affecting PMV were grouped into preoperative, intraoperative and postoperative, with factors that have a high influence, including NYHA class, acute kidney injury and mediastinitis. Differences in the number of factors examined, criteria, characteristics, and time limits of the PMV used to make the study’s results vary. Establishing guidelines regarding PMV time limits is essential according to current conditions.Keywords: coronary artery bypass graft, factors, prolonged mechanical ventilation